2018
DOI: 10.2147/ceg.s120217
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative pancreatic fistula: a review of traditional and emerging concepts

Abstract: Postoperative pancreatic fistula (POPF) remains the major cause of morbidity after pancreatic resection, affecting up to 41% of cases. With the recent development of a consensus definition of POPF, there has been a large number of reports examining various risk factors, prediction models, and mitigation strategies for this costly complication. Despite these strategies, the rates of POPF have not significantly diminished. Here, we review the literature and evidence regarding both traditional and emerging concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
138
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 156 publications
(144 citation statements)
references
References 129 publications
(130 reference statements)
3
138
1
2
Order By: Relevance
“…POPF remains a complex problem in a subset of patients due to the lack of understanding of the underlying pathophysiology of this complication and the significant variability in the recovery process. 34 Our study demonstrated that patients who suffered cardiac and respiratory complications had an increased rate of POPF compared to those who did not experience perioperative cardiorespiratory events. This supports pre-existing literature and the hypothesis that patients with a lower anaerobic threshold had a greater incidence of POPF and major intra-abdominal abscesses.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…POPF remains a complex problem in a subset of patients due to the lack of understanding of the underlying pathophysiology of this complication and the significant variability in the recovery process. 34 Our study demonstrated that patients who suffered cardiac and respiratory complications had an increased rate of POPF compared to those who did not experience perioperative cardiorespiratory events. This supports pre-existing literature and the hypothesis that patients with a lower anaerobic threshold had a greater incidence of POPF and major intra-abdominal abscesses.…”
Section: Discussionmentioning
confidence: 54%
“…A correlation between increased cardiopulmonary complications and POPF was also identified in this study. POPF remains a complex problem in a subset of patients due to the lack of understanding of the underlying pathophysiology of this complication and the significant variability in the recovery process . Our study demonstrated that patients who suffered cardiac and respiratory complications had an increased rate of POPF compared to those who did not experience perioperative cardiorespiratory events.…”
Section: Discussionmentioning
confidence: 62%
“…Generally, POPF is first identified on 1-3 days after pancreatic surgery [46][47][48]. Our study showed that the time (POD 2-3) when POPF is peaked coincides with the time (POD 2-3) when penicillin G maximizes fibrogenesis in the pancreas.…”
Section: Discussionmentioning
confidence: 54%
“…There is one potential explanation for this finding. Compared to the early 2000s when the operation in this analysis was performed, there has been notable progress in the pancreatic anastomosis procedure and in both intra-and postoperative management [22]. These recent advances may account for the discrepancy between the POPF rate in our study and those of our recent surgical results.…”
Section: Discussionmentioning
confidence: 62%